Influence of social media on the eating behavior of adult women: an observational study - Luz, Michele Borges da; Reis, Julia Novais; Pereira, Sonia Maria Soares Rodrigues; Frangella, Vera Silvia (O Mundo da Saúde, 2024)
This article aimed to identify the influence of social media in shaping eating behavior and its consequences in the lives of adult women, in addition to evaluating the perception of these women in relation to the search for nutritionists, comparing it with that of social media influencers. The methodology adopted was an observational, transversal and prospective approach. A link was shared on social media, allowing volunteers to participate after accepting the Informed Consent Form. The sample consisted of 312 women, aged between 18 and 50 years, social media users. A questionnaire was developed to collect information about eating behavior, participants’ interaction with social media, perception of their body, and opinions regarding nutritionists and influencers. The data were treated using absolute and relative numbers, highlighting the most significant results for each question. The results indicated that the searches carried out by adult women are not specifically related to healthy eating, with social media being a determining factor in eating behavior. Most participants seek health information from digital influencers rather than nutritionists. It was observed that the ideal of a beautiful body promoted by society is more related to the search for glamor and a sculptural body, regardless of the frustrations caused. It is concluded that the results are specific to the population studied, being a limiting factor for the generalization of data from this research.